Limiting long-term illness and its associations with mortality and indicators of social deprivation. (December 1995) - Bentham, G; Eimermann, J; Haynes, R; Lovett, A; Brainard, J
Abstract : STUDY OBJECTIVE--To examine geographical variation in limiting long-term illness in England and Wales and assesses the extent of its similarity with the distribution of mortality rates and of deprivation. DESIGN--A geographically based study using data from the 1991 census on limiting long term illness. Maps and regression analysis are used to compare the distribution of standardised illness ratios with standardised mortality ratios and indicators of social deprivation. SETTING--A total of 401 local authority districts in England and Wales. PARTICIPANTS--The population of England and Wales enumerated in the 1991 census. MAIN RESULTS--The geographical pattern of limiting long term illness shows many similarities with that of mortality but there are also some differences. Both are positively associated with indicators of social deprivation, with limiting long term illness tending to show stronger correlations, particularly in the elderly. Most of Wales and many industrial areas of northern England have higher rates of long term illness than would be expected from their mortality rates, while much of south eastern England has lower than expected rates. CONCLUSIONS--Moves towards using data on limiting long term illness instead of standardised mortality rates would have important implications for NHS resource allocations. Further assessment of the reliability of these data on self reported morbidity is required. in particular, there is a need to assess how much they reflect real differences in ill health rather than the influence of socioeconomic or cultural factors affecting the likelihood of a positive answer to the census question on limiting long term illness.